Analysis of Optimal Portfolio Formation Using a Single Index Model as a Basis for Investment Decision Making [Study on the Jakarta Islamic Index (JII) 2015-2017] - Ayun Niyawati; Wisnu Panggah Setiyono (Proceedings of The ICECRS, 2021)
The aim of this research is to know the performance ofstocks that become the member ofJakarta Islamic Index  (JII) and determine what stocks are part of the optimal portfolio.  This research is a quantitative descriptive study.  The  technique  of taking samples  is  using purpose  sampling  techniques,  with  determined  criteria.  The population  needed in this study  is  42 stocks.  After doing the sampling purposes,  the sample  is  20 stocks.  The analysis  technique used is  the Single Index Model.  The results of this study reveal that there are 5 stocks which eligible to become optimal portfolio members.  These shares are UNTR, AKRA,  UNVR,  TLKM, and ADRO.  Then the proportion offunds in each consecutive share is 31.58%,  15.18%, 28.02%, 17.7% and 7.52%.  While the portfolio of the portfolio formed (expected portfolio return) is 0. 0203 or 2. 03% with portfolio risk of0. 0006 or 0. 06%.